2011
DOI: 10.1002/adsc.201100270
|View full text |Cite
|
Sign up to set email alerts
|

A New Step Towards Solid Base Catalysis: Azidoproazaphosphatranes Immobilized in Nanopores of Mesoporous Silica

Abstract: International audienceHeterogeneous basic catalysts derived from proazaphosphatranes, known as Verkade’s superbases, were prepared for the first time by covalent immobilization onto SBA-15 silica. In order to introduce the tether to the surface, three siloxane-containing azido derivatives of the proazaphosphatranes were first synthesized (2a–c) which after post-synthetic grafting onto silica support led to the formation of hybrid materials of different basicity and steric properties, 2a–c@SBA-15. These latter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 47 publications
0
12
0
Order By: Relevance
“…149 Three siloxane-containing azido derivatives of the proazaphosphatranes (1a-c) were immobilized on SBA-15, leading to the construction of heterogeneous basic catalysts 1a-c@SBA-15 with different basic and steric properties (Fig. 128 TG results showed that the amount of functional groups was 0.8, 0.55, and 0.47 mmol g À1 of silica for 1a@SBA-15, 1b@SBA-15, and 1c@SBA-15, respectively. 128 TG results showed that the amount of functional groups was 0.8, 0.55, and 0.47 mmol g À1 of silica for 1a@SBA-15, 1b@SBA-15, and 1c@SBA-15, respectively.…”
Section: View Article Onlinementioning
confidence: 99%
See 1 more Smart Citation
“…149 Three siloxane-containing azido derivatives of the proazaphosphatranes (1a-c) were immobilized on SBA-15, leading to the construction of heterogeneous basic catalysts 1a-c@SBA-15 with different basic and steric properties (Fig. 128 TG results showed that the amount of functional groups was 0.8, 0.55, and 0.47 mmol g À1 of silica for 1a@SBA-15, 1b@SBA-15, and 1c@SBA-15, respectively. 128 TG results showed that the amount of functional groups was 0.8, 0.55, and 0.47 mmol g À1 of silica for 1a@SBA-15, 1b@SBA-15, and 1c@SBA-15, respectively.…”
Section: View Article Onlinementioning
confidence: 99%
“…18). 128 The deactivation may be caused by leaching of some active species and/or plugging of some pores with reactants and products. This is also in good agreement with phosphorus elemental analysis, pointing out that a lower loading (around 50%) for the more sterically hindered neopentyl and methoxybenzyl bases.…”
Section: View Article Onlinementioning
confidence: 99%
“…49 Simple reactions such as peptide formation 50 or addition of alcohols 51,52 or amines 53 on silylated isocyanates have also been used to form proline or prolinamide-based precursors. The use of (3-azidopropyl)triethoxysilane (AzPTES) upholsters growing interest, either to form P=N linkages through the Staudinger reaction, 54 or to create strong triazole linkers by the reaction with organic alkynes through the copper-catalyzed azide-alkyne cycloaddition reaction (termed CuAAC). This new methodology enables a very fast preparation of organo(alkoxy)silanes in high yield thanks to microwave activation.…”
Section: Synthesis Of Functio N Al O Rganosilanes Bearing O Rgano Catmentioning
confidence: 99%
“…High activities and endo/exo selectivities have been found, and M118c was reused up to 3 cycles without loss of activity. 54 Scheme 24 Diels-Alder cycloadditions with urea/thiourea-functionalized MSN Scheme 25 Diels-Alder cycloadditions with supported bases…”
Section: Acid and B Ase-cataly Zed Diels-alder Cyclo Additio Nsmentioning
confidence: 99%
“…The second strategy involves modification of mesoporous materials by the introduction of basic species on the surface of mesoporous hosts. Basic guests can be introduced by post-synthetic modification or direct synthesis; for example, organic basic species can be introduced into mesoporous silica using such methods [25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%